KEPUTUSAN PEMBELIAN MELALUI SITUS BELANJA ONLINE TERHADAP PERILAKU KONSUMTIF MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM : Studi kasus Pada Pengguna Aplikasi Shopee di Kecamatan Sambas - Muhammad Rio (Cross-border, 2019)
In line with the rapid increase in e-commerce transactions, digital payment transactions have also increased rapidly, which is reflected in the volume of use of electronic money in e-commerce transactions. The increase in volume caused the share of use of electronic money in e-commerce transactions in the fourth quarter of 2020 to reach 41.71%, far exceeding the share of using bank transfer and cash methods which only reached around 20.23% and 19.01%, respectively.